Costs of purchase, maintenance, microbiological control, and reprocessing of a reusable duodenoscope - Thiveaud, Dominique; Durand, Fanny; Hajjar, Joseph; Le Dinh, Emma; Metz, Vanessa; Napoleon, Bertrand; Plessis, Céline; Prat, Frédéric; Vanbiervliet, Geoffroy; Durand-Zaleski, Isabelle; Ponchon, Thierry (Endoscopy International Open, 2023)
Background and study aims The costs of reusable endoscope reprocessing have been evaluated, yet external validity of the findings remains challenging. The aim of this study was to assess the costs of purchase, maintenance, microbiological control, and reprocessing of a reusable duodenoscope per endoscopic retrograde cholangiopancreatography (ERCP) in France. Study findings exclude the costs of infection, downtime due to breakdown, reprocessing single-use material disposal, and device disposal, all of which should also be considered.Materials and methods The study encompassed both observational and theoretical approaches. Observational data were collected in four hospitals, from December 2019 to December 2020, with an ad hoc survey, based on 2016 and 2018 national guidelines for duodenoscope reprocessing. Costs were modeled, using the same guidelines, assuming a mean workload of 223 ERCP/duodenoscope/year. Results The mean observed cost of purchase, maintenance, microbiological control, reprocessing (human resources and consumables), and overhead (additional 35%) with a reusable duodenoscope was €80.23 (standard deviation €3.77) per ERCP. The corresponding mean theoretical cost was €182.71 for manual reprocessing without endoscope drying cabinet (EDC), €191.36 for manual reprocessing with EDC, €235.25 for automated endoscope reprocessing (AER) without EDC, and €253.62 for AER with EDC. Conclusions Because procedures, equipment, volume activity, number of duodenoscopes, human resources, and internal work organizations are hospital-dependent, observed costs varied between hospitals. Theoretical costs were higher than observed costs, showing that the theoretical approach is not sufficient. Hypotheses to explain the difference between the two approaches include failing to measure some costs in the survey and challenges in guideline implementation.
Keywords: Cholangioscopy; Pancreatoscopy; Quality and logistical aspects; Hygiene; Pancreatobiliary (ERCP/PTCD); Quality and logistical aspects